The Association Between Visceral Adiposity Index and Worsening Renal Function in the Elderly - Lei, Li; Dai, Lei; Zhang, Qiuxia; Lu, Junyan; Tang, Yongzhen; Xiao, Min; Li, Guodong; Yan, Shaohua; Li, Xiaobo; Chen, Yejia; Chen, Yaode; Li, Yun; et al. (Frontiers in Nutrition, 2022)
Background: Visceral adiposity index (VAI) is an indicator of visceral fat accumulation and dysfunction. However, little is known about whether VAI is associated with worsen renal function (WRF) in the elderly. Therefore, our study aimed to explore the association between VAI and WRF among the elderly population. Methods: 5583 elderly participants (aged ≥ 65 years) who participated in the annual health checks at least twice between January 2017 and July 2021 were enrolled and divided into 4 groups according to the VAI quartiles. The primary endpoint was incident chronic kidney disease (CKD), defined as incident estimated glomerular filtration rate (eGFR) < 60 mL/min/1.73m2. The secondary endpoint was rapid kidney function decline (RKFD), defined as decline in eGFR of 40%. To evaluate the association between VAI and WRF, three Cox regression models were conducted, where VAI was treated as a continuous variable and a categorical variable (Q1 as reference), respectively. Subgroup analysis in participants with different baseline characteristics was also performed. Results: During a median of 2.46 years follow-up, 931 (16.68%) participants developed CKD. After fully adjusting for confounding factors, VAI was significantly associated with incident CKD (HR, 1.052; 95% CI: 1.029-1.076, P<0.001), as well as RKFD (HR, 1.077; 95% CI: 1.041-1.114, P<0.001). Moreover, compared to those with the lowest VAI quartiles, subjects with the highest quartiles had a higher risk of incident CKD (HR, 1.286; 95% CI: 1.033-1.601, P = 0.024), as well as RKFD (HR, 1.895; 95% CI: 1.086-3.307, P = 0.025). The risk of incident CKD also tended to increase with elevated VAI quartiles (all P for trend < 0.05). This positive association remained consistent among participants with different genders, baseline weights or kidney functions. Conclusion: In our study, elevated VAI was associated with increased risk of incident CKD and RKFD in the elderly population.